The selection of essential oils from the flowers of Heliantnus tubersrosus, determination their composition and structure (Experimental biology, 2015)
Nowadays, many drugs are made from plants. Plants are the source of different organic components. So the great theoretical and practical interest are the search and selection of BAS from plants, as well as use in medicine. the results of the determination of structure and composition, as well as a selection of essential oils of flowers HELIANTNUS TUBERSROSUS. Analysis of a gas chromatograph with a mass spectrum detektrom Agilent6890/5973N. As a result of the Tashkent region of Jerusalem artichoke flower essential oil output stood at 0.5%, but from Jerusalem artichoke flower of Almaty oblast is 0.37%. The main components are: 1R-Alpha pinene, Alpha pinene and other essential oils
Keywords: biologicall; active substances; essential oils; chromatographic method; mass spectrum